Ectopic Pregnancy due to Hydroallantois in a Crossbred Cow-A Case Report - KRISHNAKUMAR, K; PALANISAMY, M; CHANDRAHASAN, C; PRABAHARAN, V; RAVIKUMAR, K (The Indian Journal of Animal Reproduction, 2023)
A case of Ectopic Pregnancy due to hydroallantois in a Crossbred Cow has been discussed.